Impact of Frequency Reuse and Flexible Cell Association on the Performance of Dense Heterogeneous Cellular Networks Using Dual-Slope Path Loss Model - Khurram Shehzad; Noor Muhammad Khan; Junaid Ahmed (IEEE Access, 2019)
Densifying low-power/small base stations (SBSs) in support of overlaid macro BSs (MBS) is getting significant consideration as a viable solution for meeting the rapidly increasing capacity demands of emerging wireless networks. Given the disparity in transmit power of BS tiers, load balancing strategies have achieved paramount importance as they ensure balance of user access load amongst BS tiers and assist in availing maximum potential of multi-tier networks. Moreover, it is also essential to utilize efficient interference management schemes to account for the excessively increasing interference in the deployed networks. There is a plethora of literature available on the analysis of dense multi-tier networks that undertake various load balancing and interference management mechanisms but they are strictly limited to single slope (SS) path loss model (PLM). Furthermore, it is also well-known in literature that SS-PLM leads to inaccuracies in estimating the performance of dense networks owing to the simplistic approach of estimating the path loss. To overcome the limitations of SS-PLM, in our work, we have employed DS-PLM to study and analyze the performance of a two-tier dense cellular network that permits flexible user association using SBS biasing in conjunction with a simple frequency reuse mechanism. A comparison of SS-PLM with DS-PLM is performed for tier association probability and coverage probability, which shows that there is significant difference in the estimated overall network performance of our proposed scheme, as compared to SS-PLM. The results clearly signify the benefits of utilizing both load balancing and interference management mechanisms under DS-PLM, and give critical design insights for finding optimal parametric values in cellular planning.